HnRNP R negatively regulates transcription by modulating the association of P‐TEFb with 7SK and BRD4. (20th July 2022) - Ji, Changhe; Deng, Chunchu; Antor, Katharina; Bischler, Thorsten; Schneider, Cornelius; Fischer, Utz; Sendtner, Michael; Briese, Michael
Abstract: The P‐TEFb complex promotes transcription elongation by releasing paused RNA polymerase II. P‐TEFb itself is known to be inactivated through binding to the non‐coding RNA 7SK but there is only limited information about mechanisms regulating their association. Here, we show that cells deficient in the RNA‐binding protein hnRNP R, a known 7SK interactor, exhibit increased transcription due to phosphorylation of RNA polymerase II. Intriguingly, loss of hnRNP R promotes the release of P‐TEFb from 7SK, accompanied by enhanced hnRNP A1 binding to 7SK. Additionally, we found that hnRNP R interacts with BRD4, and that hnRNP R depletion increases BRD4 binding to the P‐TEFb component CDK9. Finally, CDK9 is stabilized upon loss of hnRNP R and its association with Cyclin K is enhanced. Together, our results indicate that hnRNP R negatively regulates transcription by modulating the activity and stability of the P‐TEFb complex, exemplifying the multimodal regulation of P‐TEFb by an RNA‐binding protein. Synopsis: The RNA‐binding protein hnRNP R inhibits P‐TEFb‐mediated phosphorylation of RNA polymerase II, thereby modulating transcription. P‐TEFb remodelling and release from 7SK in an hnRNP R‐dependent manner contribute to this effect. Cells lacking hnRNP R show increased transcription accompanied by enhanced phosphorylation of Serine 2 of the C‐terminal domain of RNA polymerase II. Deficiency of hnRNP R induces release of P‐TEFb from the inhibitory non‐coding RNA 7SK. Cyclin T1 is destabilized upon loss of hnRNP R, and Cyclin K interaction with CDK9 is enhanced. Transcriptome alterations overlap in cells lacking hnRNP R or 7SK. Abstract : The RNA‐binding protein hnRNP R inhibits P‐TEFb‐mediated phosphorylation of RNA polymerase II, thereby modulating transcription. P‐TEFb remodelling and release from 7SK in an hnRNP R‐dependent manner contribute to this effect.